„Opowieść o krzyżu żelaznym” jako źródło do dziejów wojny bułgarsko-węgierskiej z lat 894-896 - Leszka, Mirosław J. (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2016)
The Tale of the Iron Cross does not form a primary source for the studies on history of the Bulgaro-Hungarian conflict 894-896. However, it deepens our knowledge on its memory in the Bulgarian society as it presents, to a certain degree, the wiews of the medieval Bulgarians ona war as a notion. The paper is supplemented by the Polish translation of the fragments of the Tale of the Iron Cross (by Jan M. Wolski) with the Old Church Slavonic original.